An outbreak of SARS‐CoV‐2 on a transplant unit in the early vaccination era. Issue 2 (25th January 2022) - Roberts, Scott C.; Foppiano Palacios, Carlo; Grubaugh, Nathan D.; Alpert, Tara; Ott, Isabel M.; Breban, Mallery I.; ,; Martinello, Richard A.; Smith, Cindy; Davis, Matthew W.; Mcmanus, Dayna; Tirmizi, Samad; et al.
Abstract: Background: Solid organ transplant recipients are at increased risk of COVID‐19‐associated morbidity and mortality. Aims: We describe a nosocomial outbreak investigation on an immunocompromised inpatient unit. Methods: Patients positive for SARS‐CoV‐2 were identified. An epidemiologic investigation was assisted with whole genome sequencing of positive samples. Results: Two patients were identified as potential index cases; one presented with diarrhea and was initially not isolated, and the other developed hypoxemia on hospital day 18 before testing positive. Following identification of a SARS‐CoV‐2 cluster, the unit was closed and all patients and staff received surveillance testing revealing eight additional positive patients and staff members. Whole genome sequencing confirmed an outbreak. Enhanced infection prevention practices mitigated further spread. Asymptomatic patients with COVID‐19 were successfully treated with bamlanivimab. Discussion: Preventing SARS‐CoV‐2 outbreaks in transplant units poses unique challenges as patients may have atypical presentations of COVID‐19. Immunocompromised patients who test positive for SARS‐CoV‐2 while asymptomatic may benefit from monoclonal antibody therapy to prevent disease progression. All hospital staff members working with immunocompromised patients should be promptly encouraged to follow infection prevention behaviors and receive SARS‐CoV‐2 vaccination. Conclusion: SARS‐CoV‐2 outbreaks on immunocompromised units can be mitigated through prompt identification of cases and robust infection prevention practices.